Edukasi Manajemen Stres untuk Meningkatkan Pengetahuan Kesehatan Mental Remaja di SMPN 19 Palu - MOHAMAD FIKRIYANTO H. KILO; Mayumi; Adama Maydinar Zaidah AS; Ragi Lintang Salwa Nadira; Alfanda Jihan (LPPM Universitas Widya Nusantara, 2025)
Mental health is a crucial aspect of adolescent life, given that adolescence is a period full of physical, emotional, and social developmental challenges. The high incidence of mental health issues among adolescents is believed to be linked to their limited knowledge about stress management. Health education for adolescents is essential to prevent the spread of mental health problems among this age group. This initiative aims to provide information that helps students recognize the symptoms of mental health issues. The method used in this community service activity is a Pre-Experimental Design with a One-Group Pretest-Posttest Design approach. This community service activity was conducted at SMP Negeri 19 Palu on June 18, 2025, by providing health education through lectures and discussions. The target of this activity was class VIII B students, with 15 participants. The evaluation results showed a significant improvement through pre-test and post-test with an average score of 53%, indicating that the health education conducted successfully enhanced students' knowledge in understanding mental health. The conclusion drawn from this activity is that it had a positive impact on students at SMP Negeri 19 Palu in improving their knowledge about mental health.